Effect of service learning module for teaching artificial intelligence on pre-service teachers' practical knowledge and motivation and students' attitudes - Pu, Song (2021)
Many universities and schools in China attempted to introduce artificial intelligence (AI) subjects in pre-service teachers’ (PSTs) training and primary school students’ education. It was observed that the traditional PSTs’ training modules were not entirely successful in improving their practical knowledge and motivation as well as their students’ attitudes toward AI. In particular, PSTs’ practical knowledge was very limited, and they were less motivated to teach with the assistance of AI. It was also found that primary school students’ attitudes toward AI declined as they grew older. Hence, further studies on new AI training modules or interventions very important. The objective of this study is to develop a service-learning module for PSTs teaching AI subjects using Design and Development Research (DDR) approach. It is designed to examine the effects of service-learning module on PSTs' practical knowledge and motivation in relation to AI as well as to explore primary school students' attitudes toward AI in China. In order to examine the module’s effects on the target group mentioned prior, experimental research was carried out in which the research conformed to the quasi-experimental non-randomised pre-test and post-test control group design. A questionnaire was devised in order to obtain data regarding the pre-service teachers' (PSTs) practical knowledge and motivation, and primary school students' attitudes in determining the effects of service-learning module. For this purpose, the experimental group was subjected to the service-learning module intervention, whereas the control group was taught using the educational practice training module (traditional module) as per routine in their normal classrooms. Participants in this study were 60 PSTs (12 males and 48 females) and 107 primary school students in grade six (50 males and 57 females). The pre-service teachers (PSTs) were divided into experimental and control group, in which the same was applicable for the primary school students. AI subjects were taught by the pre-service teachers (PSTs) in both groups in which the students were assigned to respectively. Tests were run in order to guarantee the validity and reliability of the questionnaire being used in this research project. Additionally, due to the target groups being native Chinese, the questionnaire was translated from English to Chinese using the the Brislin back-translation method. Data was collected pre and post intervention. In accordance with the assumptions and conditions of analysis method, paired sample t-test and Wilcoxon's Sign Rank Test were used to investigate the differences between pre-test and post-test, and independent samples t-test and Mann-Whitney U test were conducted to explore the differences between the control group and the experimental group. This study found that the service-learning module had good content validity based on expert judgement, and the module had a positive effect on the pre-service teachers’ (PSTs) practical knowledge and motivation, as well as the primary school students’ attitudes toward artificial intelligence (AI) with a score of (p< 0.05). Furthermore, the service-learning module was found to be more effective than the traditional educational practice training module in improving the three (psychological) variables mentioned above. Additionally, although the traditional educational practice training module had a positive effect on the PSTs' practical knowledge to a certain extent (p< 0.05), it did not significantly improve their motivation and the primary school students’ attitudes toward AI (p> 0.05). The findings of this study will contribute to the pre-service teachers' (PSTs) training and the artificial intelligence (AI) course design in primary education, as well as help primary school students better understand AI concepts and improve their attitudes toward it. This study provides valid data, technical support and training methods to improve the PSTs’ practical knowledge and motivation in China, and it also provides a platform that combines academic context and skills subsequently merging them into a real teaching situation. Last but not least, this research provides evidence that using service-learning module improved pre-service teachers' (PSTs) practical knowledge and motivation and primary school students’ attitudes toward artificial intelligence (AI) subjects, in line with promoting students’ development being a new value orientation of service-learning theory. This research also provides evidence and examples for PSTs training, as well as practical implications on how to improve primary school students’ attitudes in the training and learning of AI subjects.